Green wood bio-adhesives from cellulose-derived bamboo powder hydrochars - Yong-Xing Chen; Han-Song Zhu; Fan Gao; Huan-Ran Xiong; Huan Yang; Zhi-Xiang Xu; Pei-Gao Duan; Li-Jun Zheng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

The properties of Chinese Baijiu distilled spent grain-derived hydrochar: effect of in situ deep eutectic solvents formation during hydrothermal carbonization - Huan-Ran Xiong; Fan Gao; Yi Tan; Yong-Xing Chen; Zhi-Xiang Xu (Journal of Environmental Chemical Engineering, 2024)

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

Hydrochar-based facile and greenwood bio-adhesives production from distilled spent grain - Zhi-Xiang Xu; Huan-Ran Xiong; Rui Dou; Yi Tan; Yong-Xing Chen; Li-Jian Leng (Chemical Engineering Journal, 2024)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

Remotely assessing and monitoring coastal and inland water quality in China: Progress, challenges and outlook - Yujiu Xiong; Yili Ran; Shaohua Zhao; Huan Zhao; Qixuan Tian (Critical Reviews in Environmental Science and Technology, 2020)

A new sesquiterpene from the gorgonian coral Menella sp. - Qi Peng; Fen Liu; Huan Sun; Xiao-Jian Liao; Mei-Ran Feng; Ting-Ting Liu; Zheng-Xiong Xu; Jun Zhang; Shi-Hai Xu (Natural Product Research, 2016)